The sinicization of Chinese religions: from above and below - Madsen, Richard (Religion in Chinese societies, 2021)
"Since its announcement by Xi Jinping in 2015, "Sinicization" has become the slogan that guides Chinese official policy towards religion. What does it mean? What effects is it having on Chinese religions? Where will it lead? This book, with contributions from experts in the major religious traditions in China, is one of the first in English that answers these questions. From the top down, Sinicization is a project to control all forms of religion in China, even ancient indigenous forms, to make them conform to the demands of its Party-State. From the bottom up, however, religious believers are using the slogan either to sincerely attempt to adapt traditional practices to their modern cultural context or to protect their faith by offering lip service to government demands - or some combination of the two"--